The Occurrence of Anorexia and Nervous Bulimia in Juvenile Dancers in Dourados Ms Brazil - Carneiro, Ronilze Almeida (2012)
Introduction: Eating disorders increased in the early 1970s when the slim body shape fitted the aesthetic standards practiced by models and dancers and by women in general. Eating disorders were detected in the above-mentioned population who was obsessed by the necessity of having a slim body. Aim: Current investigation focuses on the existence or not of risk factors by eating disorders in the behavior of dancers in Dourados MS Brazil. Materials and methods: Eating Attitudes Test (EAT-26) and Bulimic Investigation Test Edinburgh (BITE) were employed to evaluate disorder risks. Results: Fifty-seven dancers, aged between 10 and 20 years old, practicing classical and contemporary ballet, were evaluated. Further, 38.9% belonged to Academy A; 43.85 belonged to Academy B and 17.54% belonged to Academy C. Mean weight of the samples was 49.5kg DP±9.55kg; mean height 1.60m DP±0.09m; BMI 19.3kg/m² DP±2.3kg/m². Conclusion: Two teenagers suggested a score favorable to eating behavior risk for nervous anorexia, whereas the other dancers revealed no score or normal score for eating disorders for anorexia and bulimia.